2006
DOI: 10.1136/emj.2004.022392
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle trauma: analysis of injury profiles by road-user category

Abstract: Background: Vehicle accidents in Greece are among the leading causes of death and the primary one in young people. The mechanism of injury influences the patterns of injury in victims of vehicle accidents. Objective: Identification and analysis of injury profiles of motor-vehicle trauma patients in a Greek level I trauma centre, by road-user category. Patients and methods: The trauma registry data of Herakleion University Hospital of adult trauma patients admitted to the hospital after a vehicle accident betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
48
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 17 publications
16
48
2
7
Order By: Relevance
“…Interestingly, a substantial part of the patients (39%) have injuries to their trunk or spine as an effect of blunt direct trauma or hyperflexion/extension. These numbers are comparable with the numbers of traffic accidents (30-65%) [8,9]. Some sports are associated with specific types of injuries, e.g.…”
Section: Trauma Mechanisms and Injuries Associated With Go-kartingsupporting
confidence: 67%
“…Interestingly, a substantial part of the patients (39%) have injuries to their trunk or spine as an effect of blunt direct trauma or hyperflexion/extension. These numbers are comparable with the numbers of traffic accidents (30-65%) [8,9]. Some sports are associated with specific types of injuries, e.g.…”
Section: Trauma Mechanisms and Injuries Associated With Go-kartingsupporting
confidence: 67%
“…With respect to the pattern of injury seen in motorcyclists, while the predominance of males among motorcycle victims has been reported elsewhere, 15 the pattern of injury seen in this study differs markedly from that reported internationally. 16 Whereas Markogiannakis' s large study of Greek road crashes found craniocerebral injuries to predominate among Greek motorcyclists, our study found the incidence of such injury to be relatively low. Indeed, across a range of measures the relative severity of injury of motorcyclists was strikingly low.…”
Section: Patterns Of Injury and Orthopaedic Managementcontrasting
confidence: 39%
“…The latter probably does not reflect that commuting by car is more dangerous than riding a motorcycle, but rather that motorcycle riding is more strongly associated with traumatic brain injuries than with TSCI. 9 Anyhow, our results strongly suggest the necessity for implementing more effective prevention programmes directed mainly towards young males in Greece, aiming to change their destructive driving culture.…”
Section: Impairmentmentioning
confidence: 74%